ENHANCING OF IMMUNE RESPONSE AGAINST NEWCASTLE DISEASE VIRUS FOR BROILER FEEDS ON ZINC-METHIONINE - Wejdan. M. A.; B. H. Ali (The Iraqi Journal of Agricultural science)
This study aimed to determine whether zinc methionine supplements have a beneficial effect on the immune response in broilers vaccinated against Newcastle disease (ND). A total of 120 broiler chicks were randomly divided into 6 groups. G1 were fed a basal diet and kept as a negative control G2 and G3 were fed 90 mg/kg of zinc methionine in a basal diet. The two groups were vaccinated with killed and live NDV groups 2 and 3 respectively.  Group 3 consisted of chickens vaccinated with live ND vaccine in drinking water, while Group 4 consisted of chickens fed with zinc methionine supplementation 90 mg/kg of basal diet, but not vaccinated (positive control). G5 and G 6 consisting of chickens were vaccinated as mentioned in G2 and G3. The titer of immunoglobulin G (IgG) was measured as a parameter for the immunological status of chickens during the experiment. Results reveal that the titer of IgG against ND was increased in the G2, G3, and G5, in contrast, the titer of IgG against ND was higher in groups of chicken feds on zinc methionine. Antibody titer of IgA against ND was increased in G2 and G5 with significant differences (P<0.05), increase in the titer of IgA was reported in G2 after treatment. The bursal index and spleen index at 25 days have significant results and the G2 and G3 consider the best groups compared with another groups.